2023
DOI: 10.3390/economies11070182
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Innovation on Economic Growth, Foreign Direct Investment, and Self-Employment: A Global Perspective

Abstract: This paper aims to investigate the impact of innovation on three macroeconomic indicators: GDP, self-employment, and foreign direct investment (FDI). The study analyses a sample of 120 countries using the Global Innovation Index (GII) and its constituent sub-indices and pillars, which provide a holistic evaluation of national innovation. Gross domestic product (GDP) per capita measures a country’s economic output, self-employment assesses entrepreneurial activity, and FDI indicates confidence in a country’s ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…• Innovation as a Catalyst for Economic Growth Innovation is a critical component of economic growth and development (Snyder, 2019). It leads to new products, improved services, and more efficient processes, all of which contribute to economic prosperity (Dempere et al, 2023).…”
Section: • Understanding Strategy and Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…• Innovation as a Catalyst for Economic Growth Innovation is a critical component of economic growth and development (Snyder, 2019). It leads to new products, improved services, and more efficient processes, all of which contribute to economic prosperity (Dempere et al, 2023).…”
Section: • Understanding Strategy and Innovationmentioning
confidence: 99%
“…According to Dempere et al (2023) Several case studies illustrate the successful application of strategy and innovation. Apple Inc.'s approach to product development and marketing is a prime example.…”
Section: • Understanding Strategy and Innovationmentioning
confidence: 99%
“…The ability to innovate is increasingly crucial in today's rapidly evolving world. Various researchers, such as Ciocanel and Pavelescu (2015), Dempere et al (2023), and Marto and Puertas (2023), have reported that innovation drives progress, competitiveness, and adaptability across various sectors including technology, business, healthcare, and education. In a constantly changing landscape, companies must innovate to stay ahead of the curve, meet customer demands, and solve emerging challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The Global Innovation Index (GII) ratings provide an internationally recognized framework for comparing the innovative capacity and performance across different economies. The GII is an interactive instrument that provides a valuable framework for evaluating regional innovation systems, enabling policymakers, researchers, and businesses to identify strengths, weaknesses, and areas for improvement with a high significance in assessing innovation systems (Kowalska et al 2018;Dempere et al 2023;Marti and Puertas 2023). The model of innovation systems presented in the GII offers a holistic approach that considers the multifaceted nature of innovation (Li et al 2023).…”
Section: Introductionmentioning
confidence: 99%